Pilot randomized active-placebo-controlled trial of low-dose ketamine for the treatment of multiple sclerosis-related fatigue - Fitzgerald, Kathryn C; Morris, Bridget; Soroosh, Aurash; Balshi, Alexandra; Maher, Dermot; Kaplin, Adam; Nourbakhsh, Bardia (Multiple sclerosis, 2021)
Fatigue is the most common symptom of MS and has no effective pharmacotherapy. To determine the tolerability, safety, and efficacy of low-dose ketamine infusion for MS-related fatigue. In this double-blind, randomized, active-placebo-controlled trial, 18 subjects with multiple sclerosis (MS) and reported fatigue received a single intravenous infusion of ketamine (0.5 mg/kg) or midazolam (0.05 mg/kg). The primary outcome was change in Daily Fatigue Severity (DFS) for 7 days following the infusion. Secondary outcomes included Fatigue Severity Scale (FSS) and Modified Fatigue Impact Scale (MFIS) measured up to day 28 post-infusion. We analyzed changes in all outcomes using mixed-effect models. In total, 18 participants were enrolled; 67% participants received ketamine. Side effects of ketamine were transient. No change in the DFS was observed after 7 days (-0.10 point; 95% confidence interval (CI): -0.32, 0.12; = 0.40). We observed a trend in reduced FSS scores at 1 week (-5.2 points; 95% CI: -10.4, 0.14; = 0.06) and a clinically and statistically significant reduction in MFIS score at day 28 (-13.5 point; 95% CI: -25.0, -1.98; = 0.04). Ketamine infusions were safe and well-tolerated. While no change in DFS after 7 days was observed, secondary analyses suggest a benefit of ketamine infusion for reduction of longer term fatigue severity in people with MS.